(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Creutzfeldt Jakob Disease (CJD) is an incurable, invariably fatal, rapidly progressive neurodegenerative disease caused by an abnormal isoform of a cellular glycoprotein known as the prion protein. CJD occurs worldwide, estimated annual incidence is about one case per million populations per year. Sporadic (sCJD) is a human prion disease; infection with this disease usually leads to death within one year of onset of illness. The characteristic clinical and diagnostic features of rapidly progressive dementia, myoclonus, visual or cerebellar signs, pyramidal and extrapyramidal signs, akinetic mutism and positive result on the presence of 14-3-3 protein in CSF assay, typical EEG features and MRI findings of brain are highly suggestive of diagnosis. Biopsy of brain for histopathological examination is more specific and confirmatory for diagnosis. This article reports a 65 years old lady of sCJD who was diagnosed by characteristic findings of MRI of brain, Electro-encephalography (EEG) and cerebrospinal fluid (CSF) assay at National University Hospital (NUH) Singapore and now admitted at United Hospital Limited (UHL) Dhaka for palliative and supportive management Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 141-144